Left retroperitoneal abscess caused by injury of the right knee. Issue 3 (28th January 2020) - Imai, Chie; Fujino, Hisanori; Nomura, Anryu; Sumimoto, Shinichi
Abstract: Minor trauma rarely triggers a retroperitoneal abscess. The patient' history, careful evaluation of their symptoms, and general examination with a detailed inspection of the skin are helpful to diagnose retroperitoneal abscess. Abstract : Minor trauma rarely triggers a retroperitoneal abscess. The patient' history, careful evaluation of their symptoms, and general examination with a detailed inspection of the skin are helpful to diagnose retroperitoneal abscess.